T11TS repress gliomagenic apoptosis of bone marrow hematopoietic stem cells. Issue 1 (24th March 2017) - Mondal, Somnath; Hazra, Iman; Datta, Ankur; Sk Md, Omar Faruk; Moitra, Saibal; Tripathi, Santanu Kumar; Chaudhuri, Swapna
Abstract : Combating gliomagenic global immunosuppression is one of the emerging key for improving prognosis in malignant glioma. Apoptosis plays a pivotal role within the adult hematopoietic system particularly in regulating the cells of immune system. Gliomagenic regulation of apoptotic mediators within bone marrow milieu has not been elucidated. We previously demonstrated that administration of membrane glycopeptides T11 target structure (T11TS) not only rejuvenate bone marrow hematopoietic stem cells (BMHSCs) from glioma mediated hibernation by inhibiting gliomagenic overexpression of Ang‐1/Tie‐2 but also stimulate glioma mediated diminution of expression CD34, c‐kit, and Sca‐1 markers. In the present study, we investigated the impact of glioma on apoptotic signaling cascades of BMHSCs and consequences following T11TS therapy. Bone marrow smear and Annexin V staining confirm gliomagenic acceleration of apoptotic fate of BMHSCs whereas T11TS treatment in glioma‐bearing rats disrupted apoptosis of BMHSCs. Flowcytometry, immunoblotting, and immunofluorescence imagining results revealed multi potent T11TS not only significantly downregulates gliomagenic overexpression of Fas, Fas L, Bid, and caspase‐8, the pro‐apoptotic extrinsic mediators but also strongly inhibits cytosolic release of cytochrome‐c, Apf‐1, and Bax to deactivate gliomagenic caspase‐9, 3 the key intrinsic apoptotic mediators followed by up modulation of anti‐apoptotic Bcl‐2 in glioma associated HSCs. T11TS is also able to diminish the perforin‐granzyme B mediated apoptotic verdict of BMHSCs during gliomagenesis. The anti‐apoptotic action of T11TS on glioma associated BMHSCs provide a crucial insight into how T11TS exerts its immunomodulatory action against glioma mediated immune devastation. Abstract : T11TS inhibits gliomagenic acceleration of premature apoptosis of bone marrow hematopoietic stem cells by repressing extrinsic, intrinsic, and granzyme B mediated apoptogenic cascades. Flowcytometry, immunoblotting experiments and immunofluorescence imagining results revealed multi potent T11TS significantly downregulates gliomaogenic overexpression of the key apoptotic mediators of all the above three pathways.